Penyelenggaraan E-Complaint dalam Meningkatkan Mutu Pelayanan Publik (Studi Terhadap Fasilitas Layanan E-Complaint di Universitas Brawijaya) - Arnawati, Arnawati (Jurnal Ilmiah Administrasi Publik, 2018)
Brawijaya University is trying to be an educational institution that provides the best public service in various aspects. One of them is the medium of e-complaint. E-Complaint is a facility that serves complaints in the form of information and communication technology which are accessible at anytime and anywhere. The responses of the complaints can be re-accessed through the UB website (http://e-complaint.ub.ac.id). E-complaint is the inexpensive and efficient media serving complaints. In this research, a qualitative approach was used by the researcher. Based on the results of the questionnaire given to the academic community in the Faculty of Mathematics and Natural Sciences, this research found different understandings of the existence of UB e-complaint facility. The findings showed that of the 100 students who filled out a questionnaire, only 23% students were aware of the e-complaint facility, and only 4% students have used the facility, as well as, of the 30 university staffs who filled out a questionnaire, 83.33% staffs knew the facility, but only 13.33% staffs have used it, similarly, of the 27 lecturers who filled out the questionnaire, 100% were aware of the e-complaint facility, but only 18.52% lecturers have used it.